A fluorescent probe based on a Tb3+/Cu2+ co-functionalized MOF for urinary sarcosine detection - Na-Na, Sun; Yan, Bing (Analyst (London), 2018)
A novel luminescent probe based on a Tb3+/Cu2+ heterometallic metal–organic framework (MOF) was first designed for beamed monitoring of urinary sarcosine, a differential metabolite that can indicate the progression of prostate cancer (PCa). The fluorescent probe presented high selectivity towards sarcosine in urine. It also displayed good sensitivity with a comparatively low detection limit and a fast response to sarcosine within 5 min. Moreover, such high selectivity and sensitivity towards sarcosine is not subject to interference from other coexisting species in urine. At the same time, this fluorescent material also demonstrated the possibility for recycling. The excellent sensing performance of this Ln-MOF (lanthanide MOF) enables it to be further employed as a serviceable tool for PCa diagnosis and monitoring.